Pengaruh Employee Empowerment terhadap Employee Engagement Melalui Job Satisfaction pada Karyawan Corporate Secretary Bank Jatim - Rivanti Putri Kusuma Anwar (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
PT Bank Pembangunan Daerah Jawa Timur Tbk (“Bank Jatim”) is a regional-owned company engaged in banking. The main activity of this company is to collect and channel funds and provide other banking services to all customers in the East Java region.  With the tagline "Yang Terbaik Untuk Anda", Bank Jatim maximizes the best potential ranging from services to the provision of products that continue to be developed and created technology-based to achieve BPD Regional Champion. It will not be achieved without the role of optimal human resources. The purpose of this study was to test and analyze the effect of employee empowerment on employee engagement through job satisfaction in employees of the corporate secretary division of Bank Jatim Surabaya Head Office. Where the employee empowerment variable has four indicators, the four of which will be studied, namely sense of meaning, sense of competence, self determination, impact. This research is causality research with a quantitative approach. Sampling technique used saturated samples with a total of 37 respondents in the corporate secretary division of Bank Jatim Surabaya Head Office. The statistical analysis used in this research is partial least square (PLS) with the help of smartPLS 3.0 software. The results of this study explain that employee empowerment has a positive and significant effect on employee engagement, employee empowerment has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee engagement. Job satisfaction is able to mediate the relationship between employee empowerment and employee engagement.